ATTITUDE AND EVALUATION BY THE MOSCOW CITY YOUTH OF THE SYSTEM OF MEDICAL INSTITUTIONS (ON THE EXAMPLE OF CLINICS) - T. V. Smirnova; R. G. Smirnov; E. I. Tcoi; V. V. Maslyakov (Вестник университета)
Features and nature of the perception of medical institutions by the Moscow city youth have been considered. According to the results of a quantitative study (questionnaire method, N = 622) of the attitude of Moscow youth to service in medical institutions, it was concluded that, in general, young people are not sufficiently trustful of medical institutions. Among the main reasons for such a cautious attitude, respondents call insufficient equipment of clinics with high-quality equipment and organization issues. Relief gender differences have been defined: in general, according to the sample, young girls not only visit polyclinics more often than young boys, but are also more demanding to the quality of medical services provided and service. Informing the population about the positive changes in the health care system, new possibilities of medicine can serve as an incentive to change the attitude of young people to prevention and timely treatment.